2014
DOI: 10.1007/s00134-014-3433-2
|View full text |Cite
|
Sign up to set email alerts
|

Has survival increased in cancer patients admitted to the ICU? Yes

Abstract: Intensive care unit (ICU) admission of patients with cancer has long been controversial. Studies performed in the early 1990s demonstrated high mortality rates in cancer patients admitted to the ICU, especially among those with respiratory failure requiring mechanical ventilation, neutropenic sepsis, and in hematopoietic stem cell transplant (HSCT) recipients [1, 2]. Additionally, a lack of cost-effectiveness was noted and some authors argued that denial of ICU admission could avoid futile care and unwarranted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 14 publications
2
39
0
1
Order By: Relevance
“…8,9 Recent data support the use of ICU resources in these patients, with dramatically decreased mortality rates and long-term benefits. [10][11][12] Whether these trends are confirmed in allo-HSTC patients is more controversial. 13,14 Considering all recent advances in HSCT techniques and ICU management, the reappraisal of actual prognosis became crucial to identify patients who are most likely to benefit from ICU support.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Recent data support the use of ICU resources in these patients, with dramatically decreased mortality rates and long-term benefits. [10][11][12] Whether these trends are confirmed in allo-HSTC patients is more controversial. 13,14 Considering all recent advances in HSCT techniques and ICU management, the reappraisal of actual prognosis became crucial to identify patients who are most likely to benefit from ICU support.…”
Section: Introductionmentioning
confidence: 99%
“…By defending the pro viewpoint, Mokart et al [1] may be right in claiming that survival in cancer patients in general and more particularly in those with hematological malignancies has increased over the past decade. As recently reported in a prospective study including more than 1,000 hematological patients admitted to 18 ICUs from a French-Belgian network [2], overall mortality was 50 %, but more important were mortality rates in the sickest subgroups: 60 % in the case of either one vital organ failure (need for ventilation, vasopressor, or dialysis) or two vital organ failures if reversible within 7 days.…”
mentioning
confidence: 99%
“…Mokart et al [1] ascribe recent survival benefits mainly to earlier and better supportive care provided to a more selected patient population with less comorbidities and a better performance status. It is true that ICU admission within 24 h of hospital referral has been associated with improved outcome [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of patients with solid tumors, 35 studies (25,339 patients) reported ICU and hospital mortality rates of 31.2 and 38.2 %, respectively [12]. These studies confirm the impact of performance status and mechanical ventilation on mortality, but also the lack of prognostic value of variables depicting the characteristics of the malignancy [13][14][15]. Clinical consequences of these findings are of paramount importance.…”
Section: Discussionmentioning
confidence: 86%